Using Side-Scan Sonar instrument to Characterize and map of seabed identification target in punggur sea of the Riau Islands, Indonesia. - Muhammad Zainuddin Lubis; Wenang Anurogo; Hanah Khoirunnisa; Sudra Irawan; Oktavianto Gustin; Arif Roziqin (UIR PRESS, 2017)
Punggur sea has many habitats, object, and structured of seabed with hight tide and wave. Side scan sonar is an underwater acoustic instrument for identification of seabed. This research aims to classify types of seabed and measure seabed identification into the sea water with grain size (dB), location, altitude (m) and target using side scan sonar instrument. This research also uses one types of side scan sonar in one places with 3 line of collecting data to get more variant seabed. Side scan sonar data of 20 km of side-scan sonar profiling (CM2, C-MAX Ltd, UK) with altitude max 20 m and a working acoustic frequency of 325 kHz with the zone is taken in the punggur sea (104°08.7102 E, 1°03.2448 N until 1°03.3977N 104°08.8133 E). The data side scan sonar processed using max view software to display the image of the seabed. Results of seabed imagery in the punggur sea on track 1 have Objects found on the ship coordinates 03.3101N 1 ° and 104 ° 08.7362 E with the highest gain value is 6 dB, altitude 18 m on ping 75. Linear regression has y = 0.7016x+12.952 with R2 = 0.4125 (41%). Track 2 has target 1 is the sunken object on the seabed, while objects in the form of sand can be seen clearly. Objects found on the sunken object coordinates 1°02.8143 N ° and 104°08.5228 E with highest gain value is 9 dB with altitude 17.7 m and data ping 69. Linear regression has y = 0.2093+12.577 with R2 = 0.2093 (20%). Track 3 has Target 1 is the ship object on the seabed, while objects in the form of sand can be seen clearly. Objects found on the sunken object coordinates 1°02.5817 N and 104°08.7337 E with the highest gain value is 8 dB with altitude 16.5 m and data ping 3984. Linear regression has y = 0.5106x +12.84 with R2 = 0.5106 (51%). Track 1 has many targets identification results compared Track 2 and 3.